Risky Business? Entrepreneurship in the New Independent-Power Sector - Sine, Wesley D.; Haveman, Heather A.; Tolbert, Pamela S. (Administrative Science Quarterly, 2005)
Building on sociological research on institutions and organizations and psychological research on risk and decision making, we propose that the development of institutions that reduce the risks of entering new sectors has a stronger effect on the founding rates of firms using novel technologies than on firms using established technologies. In an analysis of the independent-power sector of the electricity industry from 1980 to 1992, we found that the development of regulative and cognitive institutions legitimated the entire sector and provided incentives for all sector entrants; thus, foundings of all kinds of firms multiplied rapidly but had a stronger impact on those using risky novel technologies. In contrast, the central normative institutions that developed in this sector, state-level trade associations, provided greater support for particular forms (those using established technologies) and thus increased foundings of those favored forms more than foundings of less favored forms (those using novel technologies). Our study demonstrates how institutional forces can alter the mix of organizations entering a new industry and thus contribute to diversity, as well as similarity, among organizations.